Економіка спільного використання товарів і послуг - Москальова, М. С. (ХНУРЕ, 2024)
In this thesis, I have explored the concept of the sharing economy, which is a large aspect of the current socio-economic environment. The sharing economy uses digital platforms to exchange, use and reuse resources between consumers and suppliers. The main feature is direct interaction between them, bypassing traditional hierarchical structures. The peer-to-peer (P2P) model allows participants to exchange without intermediaries, distributing power and control among all participants. Sharing relationships are based on mutual trust and reputation, which contributes to the development of a business based on joint participation. Prospects for the development of the sharing economy include the expansion of the model and its impact on the global economy, as well as obstacles to development in different countries, including Ukraine. The basis of the sharing economy mechanism is the development of an Internet platform and the visualization of reputational capital, which creates a system of distributed trust. The prospects for the development of this model promise an increase in the impact on the economy and society, regardless of the influence of government agencies or corporations, given the importance of trust and consumer feedback.
Keywords: використання товарів і послуг; послуга